Integration of WiFi and WiMAX services: Bandwidth optimization and traffic combination - Mohd Sultan, Juwita; Markarian, Garik; Benachour, Phillip (Digital Information Research Foundation, 2015)
The integration of WiFi and WiMAX will allow seamless connection between users from both systems with a greater capacity, higher bit rates and mobility access. To enable interoperability between WiFi and WiMAX a special gateway is required known as WiFi/WiMAX router. In this paper, we investigate, through the use of OPNET simulation tools, number of WiFi users or hotspots could accommodated by a WiFi/WiMAX router and a WiMAX Base Station. Further, we evaluate the use of suitable applications and network traffic combinations for all WiFi users in order to fully optimize the network within a constrained bandwidth. On top of that, subsequently to investigate more about the hybrid network, the quantity of nodes is supported to 200 users based on the same situation. This type of integration will solves many of the difficulties in last-mile implementations, which also will benefit both users and service providers.